2013
DOI: 10.4238/2013.february.28.31
|View full text |Cite
|
Sign up to set email alerts
|

Detection and expression of Bovine papillomavirus in blood of healthy and papillomatosis-affected cattle

Abstract: ABSTRACT. Papillomaviruses (PV) are double-stranded DNA viruses that can cause benignant and malignant tumors in amniotes. There are 13 types of bovine papillomavirus (BPV-1 to -13); they have been found in reproductive tissues and body fluids. Normally these viruses are detected in epithelial tissue. We looked for BPV in the blood of healthy cattle and cattle with papillomatosis, using PCR and RT-PCR. BPV types 1 and 2 were detected in 8/12 blood samples of asymptomatic bovines and in 8/9 samples from cattle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 26 publications
2
16
0
8
Order By: Relevance
“…All these data suggest a viral activity in blood cells (Stocco dos Santos et al , 1998; Araldi et al , 2013). The presence of BPV DNA sequences in peripheral blood mononuclear cells (PBMCs) was also described in the literature in both bovines (Roperto et al , 2008; Silva et al , 2013a) and equines (Brandt et al , 2008, 2011), reinforcing our results. Following studies also showed the presence of BPV transcripts and the L1 capsid protein in PBMCs, demonstrating the productive infection in blood cells (Roperto et al.…”
Section: Breaking Paradigmssupporting
confidence: 90%
See 2 more Smart Citations
“…All these data suggest a viral activity in blood cells (Stocco dos Santos et al , 1998; Araldi et al , 2013). The presence of BPV DNA sequences in peripheral blood mononuclear cells (PBMCs) was also described in the literature in both bovines (Roperto et al , 2008; Silva et al , 2013a) and equines (Brandt et al , 2008, 2011), reinforcing our results. Following studies also showed the presence of BPV transcripts and the L1 capsid protein in PBMCs, demonstrating the productive infection in blood cells (Roperto et al.…”
Section: Breaking Paradigmssupporting
confidence: 90%
“…, 1998). However, that rate can be higher, once virus infection can be asymptomatic (Araldi et al , 2013; Silva et al , 2013a). Furthermore, the absence of epidemiological studies about BPV distribution could underestimate the real percentage of infected animals, representing a notorious difficulty in attempting to develop vaccines, once we do not know the prevalent virus types in each country.…”
Section: Bpv and Bovine Papillomatosis (Bp)mentioning
confidence: 99%
See 1 more Smart Citation
“…HPV DNA is present in the blood of cervical and head and neck cancer patients; however, it is detectable also in the blood of healthy individuals (Cao et al., ; Chen et al., ; Jaberipour et al., ). Similarly, DNA and viral gene expression from different BPV types have been detected in the blood of both healthy and tumour‐bearing cattle and equids (van Dyk et al., ; Silva et al., ). However, the biological meaning of the presence of PVs in the blood is still poorly understood.…”
Section: Introductionmentioning
confidence: 97%
“…About 60% of Brazilian cattle herd are infected by BPV [2]. However, this percentage can be greater, since the virus can lead to asymptomatic infections [11,12].…”
Section: Introductionmentioning
confidence: 99%